A case study of antiaromaticity: carbomethoxy cyclopropenyl anion - BLEDA, ERDİ ATA; ALTUN, ZİKRİ (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2019)
The simplest ideas of antiaromaticity refer to regular monocyclic systems and the eigenfunctions of the Huckel Hamiltonian for 4n pi electrons in such systems. The antiaromaticity is expressed in the energy penalty for such idealized systems relative to the Huckel energy for 2n noninteracting pi pairs. Observed systems seldom achieve the regular planar geometry assumed in this picture, owing to their ability to ease the antiaromaticity penalty by departures from the regular geometry and also by export of the 4n pi electrons' charge to substituents. In this report we estimate numerical values for the stabilization derived from such departures from the structure and the charge distribution of the idealized antiaromatic cyclopropenyl anion for a specific case, 3-dehydro-3-methyl carboxylate cyclopropenyl anion 1(-) using the thermochemical scheme CBSQB3 supplemented by CCSD(T) calculations. According to the isodesmic reaction, the anion 1(-) is destabilized by about 10-15 kcal/mol relative to the saturated 3-dehydro-3-methylcarboxylate cyclopropyl anion 2(-). We propose that the anion relieves a portion of the antiaromatic destabilization by (a) pyramidalization of one carbon of the ring, and (b) export of negative charge into the ester substituent. Both of these responses are expressed in the equilibrium structure of the anion. In the course of the study we estimate the acidity of several related anions and the enthalpy of formation of their neutral conjugate acids, and describe the interconversion of 1 to the dehydrotriafulvalene anion 3(-) by reaction with CO2. [GRAPHICS] .
Keywords: Antiaromaticity; monocyclic system; cyclopropenyl anion; isodesmic reaction; homoisodesmic reaction; triafulvenone; cycloheptatrienyl anion; CBSQB3; CCSD(T); LEVEL AB-INITIO; AROMATICITY; SINGLET; PI; DELOCALIZATION; DERIVATIVES; AFFINITIES; GAUSSIAN-2; STABILITY; ENERGIES